2018
DOI: 10.1371/journal.pone.0208169
|View full text |Cite
|
Sign up to set email alerts
|

Age threshold for recommending higher protein intake to prevent age-related muscle weakness: A cross-sectional study in Japan

Abstract: Although insufficient dietary protein intake is a known risk factor for age-related muscle weakness, the optimal age at which higher protein intake is required to prevent muscle weakness is yet to be determined. Using a population-based panel survey of community-dwelling people aged 50–75 years, this cross-sectional study aimed to find the age threshold at which a higher protein intake is associated with higher muscle strength. We utilized a dataset from the Japanese Study of Aging and Retirement conducted bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
(44 reference statements)
2
8
0
Order By: Relevance
“…Meanwhile, we showed dietary total protein and animal protein intake was positively associated with AMMI, AMM, and MM among women aged ≥75, not aged 65–74. This is consistent with the results of previous experimental studies which examined the relationship between dietary protein intake and hand grip strength in Japan [ 27 ]. This result imply that dietary intervention alone might be a less effective strategy to prevent age-related loss of AMM and MM for the women aged 65–74.…”
Section: Discussionsupporting
confidence: 92%
“…Meanwhile, we showed dietary total protein and animal protein intake was positively associated with AMMI, AMM, and MM among women aged ≥75, not aged 65–74. This is consistent with the results of previous experimental studies which examined the relationship between dietary protein intake and hand grip strength in Japan [ 27 ]. This result imply that dietary intervention alone might be a less effective strategy to prevent age-related loss of AMM and MM for the women aged 65–74.…”
Section: Discussionsupporting
confidence: 92%
“…While the effect size comparing the low and moderate intakes was small for the same variables (d < 0.5). Our findings partially support the assumption that physically active older adults may require higher amounts of protein (≥ 1.2 g/ kg BM per day) than the current recommendations (0.8 g/kg BM per day) and may be a key factor in preventing the decline in muscle strength in older adults [58,59]. There have been numerous observational studies that have correlated protein intake in relation to sarcopenia to explore diet-muscle health relationships [59].…”
Section: Malessupporting
confidence: 79%
“…This lack of statistical significance might be explained in part by the imperfect HEI scoring system: as 2⋅5 ounces of total protein foods per 1000 kcal already receive the highest attainable score, further intake is going unnoticed. Various studies have already shown that people with a low intake of total protein have a lower average muscle mass and strength (37)(38)(39) . Decreased protein synthesis as a result of poor dietary intake might cause muscle fibre atrophy and a reduction of muscle mass leading to weak muscle strength, possibly providing the link of causality between low protein intake and low HGS (40) ; however, there is a controversy about the association between improvement of muscle mass or weakness with dietary protein intake in many studies (40)(41)(42)(43)(44) , which warrants further research.…”
Section: Discussionmentioning
confidence: 99%